Effect of Drought and Low P on Yield and Nutritional Content in Common Bean - Smith, Millicent R.; Dinglasan, Eric; Veneklaas, Erik; Polania, Jose; Rao, Idupulapati M.; Beebe, Stephen E.; Merchant, Andrew (Frontiers in Plant Science, 2022)
Common bean (Phaseolus vulgaris L.) production in the tropics typically occurs in rainfed systems on marginal lands where yields are low, primarily as a consequence of drought and low phosphorus (P) availability in soil. This study aimed to investigate the physiological and chemical responses of a panel of common bean genotypes and their partners for adaptation to individual and combined stress factors of drought and low P availability. Water stress and P deficiency, both individually and combined, decreased seed weight and aboveground biomass by ~80%. Water deficit and P deficiency decreased photosynthesis and stomatal conductance during plant development. Maximum rates of carboxylation, electron transport and triose phosphate utilization were superior for two common bean genotypes (SEF60 and NCB226) that are better adapted to combined stress conditions of water deficit and low P compared to the commercial check (DOR390). In response to water deficit treatment, carbon isotope fractionation in the leaf tissue decreased at all developmental stages. Within the soluble leaf fraction, combined water deficit and low P, led to significant changes in the concentration of key nutrients and amino acids, whereas no impact was detected in the seed. Our results suggest that common bean genotypes have a degree of resilience in yield development, expressed in traits such as pod harvest index, and conservation of nutritional content in the seed. Further exploration of the chemical and physiological traits identified here will enhance the resilience of common bean production systems in the tropics.